COLLABORATIVE STRATEGIC READING IMPLEMENTATION TO IMPROVE STUDENTS’ READING COMPREHENSION - Desy Olivia Riani (University of Kuningan, 2013)
Abstract: This collaborative action research is aimed to find out whether or not the implementation of Collaborative Strategic Reading (CSR) improves students' reading comprehension and also to identify students' attitude towards the implementation of CSR. CSR is reading strategy that employs four strategies namely Preview, Click and Clunk, Get the Gist and Wrap Up during students’ cooperative learning. A class of eleventh grade students of a public senior high school in Majalengka, West Java, Indonesia is participated as the participant of the study. The required data were collected through the use of questionnaire, observation checklist, and reading test. The data from the questionnaire indicated that 82% students had positive attitude toward the implementation of CSR. They feel that CSR improves their motivation in learning English and CSR brings more fun to the process of learning. Moreover, it was found from observation data that the students were actively participated during CSR implementation and they were motivated when comprehending a text by means CSR strategy. Finally, the study proved that CSR improved students’ reading comprehension. Students’ mean score of reading test in the beginning of the study was 67, meanwhile, after applying CSR as reading strategy, their mean scores improved to 88.Keywords: CSR, Reading Comprehension, Action Research.